"Spaghetti Maneuver": A useful tool in pediatric laparoscopy - Our experience - Antonio Marte; Silvia Cavaiuolo; Lucia Pintozzi; Maurizio Prezioso; Fabiano Nino; Sandra Coppola; Micaela Borrelli; Pio Parmeggiani (Wolters Kluwer Medknow Publications, 2011)
Aims: The laparoscopic "Spaghetti Maneuver" consists in holding an organ by its extremity with a grasper and rolling it up around the tool to keep the organ stable and facilitate its traction within a small space. We describe our experience with the "Spaghetti Maneuver" in some minimally invasive procedures. Materials and Methods: We successfully adopted this technique in 13 patients (5F : 8M) aged between 6 and 14 years (average age, 10) on whom we performed 7 appendectomies, 2 ureteral reimplantation and 4 cholecystectomies. In all cases, after the first steps, the appendix, the gallbladder and the ureter were rolled around the grasper and easily isolated; hemostasis was thus induced and the organ was mobilized until removal during cholecystectomy and appendectomy, and before the reimplantation in case of ureteral reimplantation. Results: We found that this technique facilitated significantly the acts of holding, isolating and removing, when necessary, the structures involved, which remained constantly within the visual field of the operator. This allowed a very ergonomic work setting, overcoming the problem of the "blind" zone, which represents a dangerous and invisible area out of the operator's control during laparoscopy. Moreover the isolation maneuvers resulted easier and reduced operating time. Conclusion: We think that this technique is easy to perform and very useful, because it facilitates the dissection of these organs, by harmonizing and stabilizing the force of traction exercised.